2015
DOI: 10.1177/0267659115586280
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygen saturation during pulsatile and non-pulsatile cardiopulmonary bypass in patients with carotid stenosis

Abstract: Pulsatile and non-pulsatile cardiopulmonary bypass (CPB) flows may have different impact on cerebral oxygen saturation in patients with restricted cerebral arterial blood supply. Twenty patients, ten diagnosed with carotid stenosis (CS, n = 10) and ten without known carotid disease (Controls, n = 10), were subjected to one period of pulsatile and one period of non-pulsatile flow (6-8 min each) during CPB at 32°C. Cerebral oxygen saturation was registered by near-infrared light spectroscopy (NIRS).The mean arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Clinically, brain NIRS has been used as a marker for cerebral oxygenation during the intraoperative management of cardiopulmonary bypass and carotid endarterectomy (8,10,11,18). It has also been investigated for use in the management of adult and neonatal ischemic brain injury (1,3,6,14) and traumatic brain injury (22).…”
mentioning
confidence: 99%
“…Clinically, brain NIRS has been used as a marker for cerebral oxygenation during the intraoperative management of cardiopulmonary bypass and carotid endarterectomy (8,10,11,18). It has also been investigated for use in the management of adult and neonatal ischemic brain injury (1,3,6,14) and traumatic brain injury (22).…”
mentioning
confidence: 99%
“…The role of carotid stenosis as a significant variable in cerebral blood supply is not clear yet, although some researchers attempted to discuss this subject. Tovedal et al 23 evaluated flow type during CPB in two groups of patients, each group comprised of 10 subjects. Despite the fact that they detected no significant changes in cerebral oxygenation between groups, the tissue oxygenation index tended to be decreased in patients with carotid stenosis in the pulsatile manner of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a high MAP would be highly recommended for the protection of the brain and the abdominal organs especially for patients with high risk of embolization. [19] That would actually be and the most obvious practice during CPB. An increase in the MAP and the maintenance of a higher blood pressure would reimburse the drop of the pressure across the stenosis [20].…”
Section: Blood Pressure During Cpb: Role and Particularitiesmentioning
confidence: 99%
“…Tovedal and colleagues found that there is no difference in cerebral oxygenation between these two techniques but MAP was decreased during pulsatile flow. [19] Similar questions might be formed about the importance of blood flow and pressure when using a roller pump, where the output remains constant, or a centrifugal pump where the output fluctuates depending on the peripheral resistance of the vessels. Finally, how would the superiority or the inferiority of pressure towards flow would be proved in cases where the former is mainly generated by the latter and not by vasoconstrictors or vasodilators?…”
Section: Blood Pressure During Cpb: Role and Particularitiesmentioning
confidence: 99%